ANGIOPLASTIC STENOSIS IN SPONTANEOUS BILATERAL CAROTIC ARTERY DISSECTION: A CASE REPORT - Subandi, Subandi; Danuaji, Rivan; Suroto, Suroto; Mirawati, Diah Kurnia; Budianto, Pepi; Hambarsari, Yetty; Hamidi, Baarid Luqman; Prabaningtyas, Hanindia Riani; Hutabarat, Ervina Arta Jayanti; Ristinawati, Ira; Tejomukti, Teddy; Tedjo, Raden Andi Ario; Santosa, Novian Anindito; Putra, Stefanus Erdana; Hafizhan, Muhammad (MNJ (Malang Neurology Journal), 2024)
Case: A 28-years-old woman presented with sudden right extremities weakness, right sided facial droop, and not being able to speak. On examination, the patient had upper motor neuron (UMN) hemiplegia and motor aphasia. On blood laboratory, we found D-dimer level of 1068 ng/dl. A non-contrast head CT-scan and CT-angiography showed left cerebral hemisphere infarction, and bilateral carotid artery stenosis. Further investigation with transcranial Doppler demonstrated partial stenosis of internal carotid artery (ICA). On cerebral digital subtraction angiography (DSA), we observed pseudoaneurysm on the right ICA and flame-shaped appearance on the left ICA, both are common radiological finding of ICA dissection. Then we performed stenting angioplasty on bilateral ICA to provide recanalization, and aspirin 80mg q.d. and clopidogrel 75mg q.d. was initiated. Conclusion: Spontaneous dissection of the carotid artery can occur on young adults. DSA is considered as the gold standard for vascular examination, and stenting with angioplasty was performed for recanalization to prevent the progression to severe stroke.